2012
DOI: 10.1590/s0037-86822012000500011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the frequency of adverse reactions caused by antimony in the treatment of American tegumentary leishmaniasis in Governador Valadares, State of Minas Gerais, Brazil

Abstract: Introduction: Governador Valadares is an endemic area of American tegumentary leishmaniasis (ATL). The detection rate was 15.36 per 100,000 habitants from to 2006(Miranda, 2008. This study aimed to analyze the effects of age on the frequency of adverse reactions caused by antimony in the treatment of ATL in the City of Governador Valadares, State of Minas Gerais, Brazil, during 2009. Methods: Data were collected from the forms of the Information System for Notifiable Diseases, and from charts, questionnaires, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…A previous study showed that in the treatment of ATL most of adverse events occur in subjects over 50 years of age [40]. While it is an interesting observation, our trial was not powered to detect differences among subgroups and these results serve to suggest that subjects over 50 years old may be a suitable group to assess in further studies.…”
Section: Discussionmentioning
confidence: 89%
“…A previous study showed that in the treatment of ATL most of adverse events occur in subjects over 50 years of age [40]. While it is an interesting observation, our trial was not powered to detect differences among subgroups and these results serve to suggest that subjects over 50 years old may be a suitable group to assess in further studies.…”
Section: Discussionmentioning
confidence: 89%
“…9 Most data related to the disease in the elderly, defined as older than 65 years for men and 60 years for women, come from epidemiologic and clinical studies with the participation of few elderly patients. 10 In a retrospective study comparing CL in young versus senior patients, we found that patients older than 60 years were more likely to have a previous history of CL, less lymph node enlargement, and higher frequencies of ML and DL. In this study, we also documented that older patients produced less interferon (IFN)-γ and more interleukin (IL)-10 than young patients.…”
Section: Introductionmentioning
confidence: 82%
“…8 Moreover, age has been an important factor regarding side effects caused by antimony therapy. 9,10 Epidemiologic studies have pointed out that ATL occur predominantly in young subjects, a population that is more exposed to sand fly bites. 4 However, cohort studies have shown an increasing number of elderly present with CL 2,4 and it is well known that ML and DL occur more in adults than in children.…”
Section: Introductionmentioning
confidence: 99%